AH-02 Cutaneous Muscle of Javan Porcupines (Hystrix javanica) - Supratikno Supratikno; Halim Bakti Harjo; Danang Dwi Cahyadi; Srihadi Agungpriyono (Media Veteriner, 2015)
Cutaneous Muscle of Javan Porcupines (Hystrix  javanica)